NEEM – AN INVALUABLE BIORESOURCE - DR. JAYA VIKAS KURHEKAR (International Journal of Pharma and Bio Sciences, 2013)
Neem Azadirachta indica is known for its various medicinal applications and has great significance in Indian traditional medicine. In the present study, aqueous and acetone extracts of neem were analyzed for inherent components, anti-microbial activities against common pathogens and compared with standard antibiotics. Aqueous extract was effective against four Gram positive, three Gram-negative pathogens and acetone extract against three Gram positive and one Gram negative pathogens isolate. Qualitative and HPTLC analysis showed the presence of glucose, proteins, alkaloids, flavonoids, terpenes, saponins, caffeic acid, xantho-eriodictyl, silychristin, taxifolin and iso-silybin. Considering the pharmacological, broad spectrum anti-microbial activities and potential for controlling both microbial and insect pests, deliberations can be made about use of A. indica as an antimicrobial agent, dietary supplement and a prebiotic.